Pengaruh entrepreunial intention terhadap motivasi berwirausaha mahasiswa - Haryono, Arfin; Zairina, Zairina (Journal of Management and Digital Business, 2022)
Instilling entrepreneurial motivation in students is essential, as it capitalizes on students' knowledge and entrepreneurial intention in creating future young entrepreneurs. This study aimed to see how entrepreneurial intention influences entrepreneurial motivation in students of the Faculty of Economics and Business, Nazhhatut Thullab Al Muafa University. This study used 64 students as participants. Simple linear regression and descriptive statistics were utilized in data analysis. The study results show that entrepreneurial intention and motivation scores are very high. There is an influence of entrepreneurial intention on student entrepreneurship motivation. Meanwhile, entrepreneurial intention can explain 35.2 percent of entrepreneurial motivation. Recommendations for further research need to add locus of control and entrepreneurial self-efficacy to understand student entrepreneurial motivation.